The Effect of pH on Synthesis of Hydroxyapatite from Geloina Coaxans Shell - Yanti, Pepi Helza; Nia, Nia (Institut Teknologi Sepuluh Nopember, 2017)
The effect of pH on synthesis of hydroxyapatite from Geloina coaxans shell has been done by precipitation method. Geloina coaxans shells and several phosphate sources (NH4)2 HPO4 and H3PO4 were used as precursors on synthesis of HAp. Synthesis of HAp was done with molar ratio of precursors 1,67 and pH of solution were varied at 10, 12, 13, and 14. The result proved that nano-HAp can be obtained successfully and shown that pH value was a significant parameter variable on synthesis HAp that can influence crystalinity and purity of HAp. Using Schererr equation, particle size of HAp powder of (NH4)2HPO4 was 26,69 while H3PO4 was 40 nm respectively